Прелімінарна матриця соцреалістичної парадигми "дитя революції" - Вільчанська, Ю.; Завидович, В. (Філологічний дискурс, 2020)
Досліджується питання соціального вигнанства дитини (сирітства / безпритульності) в його онтологiчному значенні. Розглядається особливості формування виокремленої парадигми «дитя революції». Образ знедоленої дитини – інтерпретується, як перше втілення даної парадигми в літературі. Прослідковується специфіка формуванння парадигми «дитя революції», та вплив на це явище суспільно-історичних потрясінь. Вивчається прелімінарна кризова передісторія дитячої особистості в умовах революції як соціальної травми. Смерть дитини, піднесеної спільною справою (або захопленою новою державною ідеєю), інтерпретується як транзитивний образ європейської повоєнної літератури нового часу. This article discovers the question of social exile of a child (orphanage / homelessness) in its ontological meaning. The peculiarities of formation of the isolated paradigm «child of revolution» are considered. In addition, it considers the peculiarities of formation of divided paradigm «child of revolution». The status of «child of the revolution» demonstrates a «different» existential position: 1) spiritual orphanage; 2) the thirst for death for the sake of the idea. It is determined that, due to conditions of ideological activity, the child in a passionate love to the idea is capable to go to death; the last can be explained as unconscious suicide. The existential foundations of youthful behavior are analyzed in the prominent literary examples: V. Hugo’s homeless teenager Gavrosh, M. Ostrovskyi’s young revolutionary Pavlo Korchagin, and E. Bagrytskyi’s pioneer girl Valentyna. The question arises about children’s irrationality and the causes of tragedy of the child’s condition. Also in this article, such questions are traced: the specificity of the formation of the paradigm «child of the revolution», and the impact of social and historical upheavals on this phenomenon. Besides, the primary prehistory crisis of child’s personality in conditions of revolution that can be seen as social trauma is being studied. The main existential factors of the paradigm «child of revolution» are analyzed. The death of a child brought up by a common cause (or captured by a new state idea) is interpreted as a transitive image of modern European postwar literature.